Prevalence and factors associated with overweight in adults in Brazilian capitals and the Federal District, 2019 - Sousa, Alana Paulina de Moura (2021)
Objective: To analyze the prevalence and factors associated with overweight in Brazilian capitals and the Federal District, Brazil, 2019. Methods: Cross-sectional study, with data from the Surveillance of risk and protective factors for chronic diseases by telephone survey, 2019. Prevalence was calculated overweight and association with sociodemographic and behavioral characteristics and health status, stratified according to sex. Results: The prevalence of overweight was 55.9% (95%CI 54.9;56.9), associated in men with age of 35-44 years (PR=1.87 – 95%CI 1.65;2.12), alcohol consumption (PR=1.09 – 95%CI 1.03;1.15), and hypertension (PR=1.24 – 95%CI 1.17;1.31); and in women, associated to age 45-54 years (PR=2.03 – 95%CI 1.77;2.32), habit of watching television for 3h/day (PR=1.09 – 95%CI 1.04;1.15), and poor/very poor health status (PR=1.31 – 95%CI 1.20;1.43). Conclusion: Overweight was observed in more than half of the sample, associated with hypertension, diabetes mellitus and alcohol consumption, in both sexes.